The Use Of The Merdeka Curriculum In Teaching Arabic At United Islamic Junior High School Cahaya Hati Bukittinggi (An Analytical Study) - Nisak, Khairatun; Wahyuni, Wira (Program Studi Pendidikan Bahasa Arab, 2025)
The Merdeka Curriculum is a curriculum that creates enjoyable learning conditions for students and teachers so that learning is achieved according to students’ needs and interests. The purpose of this research is to understand the use of the Merdeka Curriculum in planning, implementing, and evaluating Arabic language teaching. The research method applied is descriptive, which focuses on studying a phenomenon in detail or distinguishing it from other phenomena. This research involved teachers and curriculum representatives at the United Islamic Junior High School Cahaya Hati Bukittinggi. The results show that in terms of design, teachers used teaching models in accordance with the Ministry of Education and Culture, producing well-prepared learning units. In terms of implementation, teachers carried out teaching using well-designed learning units, although they also used several textbooks from the previous curriculum. The assessments used were aligned with the regulations. In conclusion, the Merdeka Curriculum functions effectively in this school.